Population genomics of native maize through pooled sequencing - Freilij, Damián; Defacio, Raquel Alicia; Vera, Pablo; Puebla, Andrea Fabiana; Paniego, Norma Beatriz; Dominguez, Pia Guadalupe; Lia, Veronica Viviana (Asociación Argentina de Bioinformática y Biología Computacional, 2025)
Poster